Biochemistry of lipids, lipoproteins and membranes - Ridgway, Neale; McLeod, Roger (Elsevier, 2016)
Biochemistry of Lipids: Lipoproteins and Membranes, Volume Six, contains concise chapters that cover a wide spectrum of topics in the field of lipid biochemistry and cell biology. It provides an important bridge between broad-based biochemistry textbooks and more technical research publications, offering cohesive, foundational information. It is a valuable tool for advanced graduate students and researchers who are interested in exploring lipid biology in more detail, and includes overviews of lipid biology in both prokaryotes and eukaryotes, while also providing fundamental background on the subsequent descriptions of fatty acid synthesis, desaturation and elongation, and the pathways that lead the synthesis of complex phospholipids, sphingolipids, and their structural variants. Also covered are sections on how bioactive lipids are involved in cell signaling with an emphasis on disease implications and pathological consequences.
Keywords: Lipids -- Metabolism.; Lipoproteins -- Metabolism.; Membrane lipids -- Metabolism.; elektronické knihy; electronic books